El rol familiar y la autonomía en los niños de inicial 2 de la Unidad Educativa Dr. Gabriel Gracia Moreno - Saigua Andino, María José (2024)
The present investigation was carried out in the Educational Unit “Dr. Gabriel García Moreno” from the Guano canton, Chimborazo province, has as its main objective Analyzing the family role and autonomy of the children of Initial 2 of the Educational Unit ¨Dr. Gabriel García Moreno¨ from the Guano canton, the search for information was done in different reliable bibliographic sources such as articles, local, national and international university repositories. The methodological design used was non-experimental focused on the study of variables without manipulation, being a research with a qualitative approach that allowed the collection and analysis of data taken from the selected sample of the population corresponding to 20 students and a teacher of initial 2 of the Educational Unit “Dr. Gabriel García Moreno", the data collection technique and instrument was observation and the application of an observation sheet that consisted of 10 indicators on two scales, the first 5 items directed at the children and the next 5 items applied to the teacher. . It must be emphasized that the family plays a very important role in the development of autonomy of children in early education. The family provides a safe and supportive environment so that children can explore, experiment and learn on their own. Additionally, parents and caregivers foster autonomy by allowing children to make age-appropriate decisions and encouraging them to complete tasks on their own.